Effects of Physical therapy Management of Stress Urinary Incontinence among Postnatal Women-A quasi experimental study - Arshad, Sabiha; Waseem, Iqra; Mahmood, Tahir; Batool, Farwah; Salam, Abdul (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: During delivery, stress incontinence develops due to weakness of pelvic floor muscles. The objective of the current study was to determine the effects of physiotherapy among post-natal women having stress urinary incontinence. METHODOLOGY: This Quasi-Experimental study was conducted on 40 post-natal women in the age of 25-40 years. The data was collected using a convenient sampling technique. After an informed consent, participants were assessed on the day of the visit, and pelvic floor muscle exercises [kegel exercise] were performed. First, they were assessed on 1st visit and the final assessment was made at end of treatment by using the same physical examination. The assessment was done on 1st visit and after 12 weeks, with 3-5 sessions/week. SPSS version 20.0 was used for analysis of data and paired–t test was used for comparing pre and post intervention. RESULTS: The current study comprised 22 (55%) participants with 25-32 years of age group and 18(45%) in 32-40 years of age. The results showed that 2 (5%) had no urine leakage, while 20(50%) had 3-4 times leakage, 25(62.5%) left their pads /garments during the treatment period. Of them 18(45%) had no restriction and 15(37.5%) had some restriction in daily activities and 19 (47.5%) have fair squeeze, 12 (30%) had a weak squeeze, p-value had shown statistically significant difference at p<0.05, stating that Kegel exercise were found effective than routine interventions for the management of Stress Urinary Incontinence (SUI). CONCLUSION: Kegel exercise (Pelvic floor muscle exercises) appeared to be an effective treatment protocol for postnatal women presenting with stress urinary incontinence with statistically significant differences on pre and post intervention analysis.